1980
DOI: 10.1073/pnas.77.12.7014
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of subcomponents C1r and C1s of first component of complement: electron microscopic and ultracentrifugal studies.

Abstract: Monomeric Cis (Mr, 85,000; sso,,,4.3 S), a subcomponent of first component of complement (C),the dimer (Mr, 170,000; s20,w, 6.7 (sow, 16.3 S) reconstituted from Clq, Cir, and Cis dissociates under the conditions used for electron microscopy. Some features of the C1 complex are revealed in the dissociation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
43
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 20 publications
6
43
0
1
Order By: Relevance
“…The collagen peptide Ac(GPO) 4 -GKL-(GPO) 4 NH 2 was made by Generon Ltd. The CUB1-EGF-CUB2 fragment of C1s incorporating a C-terminal hexahistidine tag was produced in Chinese hamster ovary cells and purified by affinity chromatography on a nickelSepharose affinity column as described (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collagen peptide Ac(GPO) 4 -GKL-(GPO) 4 NH 2 was made by Generon Ltd. The CUB1-EGF-CUB2 fragment of C1s incorporating a C-terminal hexahistidine tag was produced in Chinese hamster ovary cells and purified by affinity chromatography on a nickelSepharose affinity column as described (12).…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of C1q, they form an elongated S-shaped heterotetramer with two central C1r polypeptides, linked via their catalytic domains (CCP1-CCP2-SP), each flanked by a C1s chain (4). A clue to the likely mode of binding between C1r and C1s is provided by the crystal structure of the C1s CUB1-EGF fragment (5) and structures of two related proteases of the lectin pathway of complement: the CUB1-EGF-CUB2 domains of mannan-binding lectin-associated serine protease (MASP)-2 (6) and MASP-1/-3 (7), in which polypeptides are arranged as antiparallel X-shaped dimers.…”
mentioning
confidence: 99%
“…Clq has the appearance of a bouquet of tulips (13); Clr2Cls2 resembles a rod with bent ends (5). Reassembled C1, which spontaneously re-forms when one subunit of Clq is mixed with one tetrameric subunit of Clr2Cls2 in the presence of Ca2+, has hydrodynamic properties consistent with a 1-to-i complex (ref.…”
mentioning
confidence: 99%
“…Excellent electron micrographs ofClq (1)(2)(3)(4) and ofthe Clr2Cls2 tetramer have been published (5), as well as hydrodynamic studies on Clq, Clr2Cls2, and C1 (5)(6)(7)(8)(9)(10)(11)(12). Clq has the appearance of a bouquet of tulips (13); Clr2Cls2 resembles a rod with bent ends (5).…”
mentioning
confidence: 99%
“…Electron microscopy studies of the crosslinked C1 complex showed that the tetramer is located in the cone formed by the six collagen-like stems between the globular heads and the stalk (12,13). Electron microscopy and neutron scattering studies of isolated C1s-C1r-C1r-C1s indicated an extended conformation of the tetramer in solution (14,15). However, the volume inside the C1q cone is too small to contain the entire elongated tetramer.…”
mentioning
confidence: 99%